2020
DOI: 10.33800/nc.vi15.217
|View full text |Cite
|
Sign up to set email alerts
|

Natural hybridization between two species of green Anoles: morphological and genetic evidence

Abstract: Anoles are a group of lizards that offer a wide range of opportunities to study different biological topics. In this work, we examined some aspects of the morphology from 139 individuals of green anoles collected in urban parks of Santo Domingo and the Distrito Nacional. We investigated evidence of hybridization between the two Hispaniola endemic species Anolis chlorocyanus and A. cyanostictus and the introduced species A. porcatus. We categorized the individuals in pure species and intermediates based on thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
(20 reference statements)
0
4
0
Order By: Relevance
“…(Arias 1989), which could cause declines in populations of the native lizards. Additional study of these species is necessary to help prevent declines in endemic and native species and the potential hybridization, as documented by Gabot-Rodriguez et al (2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(Arias 1989), which could cause declines in populations of the native lizards. Additional study of these species is necessary to help prevent declines in endemic and native species and the potential hybridization, as documented by Gabot-Rodriguez et al (2020).…”
Section: Discussionmentioning
confidence: 99%
“…Hispaniola (Dominican Republic and Haiti) has more than 56 documented species of Anolis (Hedges 2020) found in every land ecosystem, representing every ecomorph, and occupying several niches. Gabot et al (2020) reported the hybridization between two species of anoles on Hispaniola, where Anolis porcatus is allopatric with A. chlorocyanus and A. cyanostictus. Reyes et al (2018) produced a checklist the herpetofauna of the campus of the Autonomous University of Santo Domingo (UASD) and Sano and Montero (2018) analyzed the tree preferences of two species of anole lizards.…”
Section: Introductionmentioning
confidence: 99%
“…Aside from its occurrence across a mosaic of habitat types, this hybridization event is notable for two other reasons. First, while a few previous instances of hybridization among anole species have been recorded (Gabot-Rodriguez et al, 2020;Gorman & Atkins, 1968;Jenssen, 1977;Jezkova et al, 2013;Kohler et al, 2010;MacGuigan et al, 2017), such events are rare within the nearly 400-species Anolisclade (Losos, 2009). Second, the genetically distinct nature of the hybrid population is indicative of historic admixture followed by in situ population differentiation (Wegener et al, 2019).…”
Section: Introductionmentioning
confidence: 98%
“…Aside from its occurrence across a mosaic of habitat types, this hybridization event is notable for two other reasons. First, while a few previous instances of hybridization among anole species have been recorded (Gabot‐Rodriguez et al, 2020; Gorman & Atkins, 1968; Jenssen, 1977; Jezkova et al, 2013; Kohler et al, 2010; MacGuigan et al, 2017), such events are rare within the nearly 400‐species Anolis clade (Losos, 2009). Second, the genetically distinct nature of the hybrid population is indicative of historic admixture followed by in situ population differentiation (Wegener et al, 2019).…”
Section: Introductionmentioning
confidence: 99%